Achievement of students' language proficiency and their attitudes toward TMM online - Rattana Jangpiboonpong (Universitas Islam Malang, 2021)
This ongoing study is conducted to explore language proficiency and the attitudes of 63 first year students from Faculty of International Studies who use Tell Me More Online (TMM online) as their learning tool (Academic Year 1/2020) and the effectiveness of TMM Online in enhancing students’ English language proficiency. The evaluation results from all English courses which the students registered in the semester will be used as a research instrument to see the student progress in English language learning or their language proficiency. Questionnaires and the semi-structured interview will be also launched to acquire the attitudes of the students towards doing self-learning exercises from TMM online. The results for the first phrase of data analysis was to see the attitude towards TMM online. It was revealed that the students’ satisfaction on content, materials used, and application of TMM Online was at the satisfied level.Keywords: achievement; language proficiency; attitudes